(untitled) (Encuentros, 2018)
The identity configuration is one of the aspects that allows the subject to be characterized in order to demonstrate the training processes that take place. Narrative and lived body could offer elements, both in the configuration of the identity of the subject, as formative possibilities that expand the domains of meaning and action. The research article establishes a dialogue between Merleau Ponty, from lived body, and Ricoeur, from narrative, in the configuration of identity. The analysis of the information, from the analogical hermeneutics, throws concordances between both authors in temporality, schematism, stories or words in the nascent state, and life as text. Narrating the lived body is a way of understanding the lived experiences that helps to shape the identity of the subject as an open and continuous project of formation. Keywords: Merleau-Ponty, Ricoeur, lived body, narrative, and identity